(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The implementation of guidance and counselling services within secondary educationalinstitutions has been shown to have a beneficial effect on students’ capacity to make well-informeddecisions concerning their future career trajectories, their self-efficacy, and their academic performance.The execution of such programmes has the potential to furnish students with the chance to acquireskills that enable them to abstain from making impulsive or uninformed professional assessments, whilealso augmenting their ability to make pragmatic and self-assured decisions. The principal aim of thepresent investigation was to examine the impact of guidance and counselling interventions on thevocational selection and decision-making proficiency of secondary school pupils. The present studyemployed a convenience sampling method to select a sample of 207 participants from private andgovernment schools. The research extensively utilized primary sources in the process of compiling data.The current investigation utilized a variety of statistical methodologies, such as the Fischer test,ANCOVA, t-TEST, and Two-way ANOVA. The study’s results have provided valuable insights for schoolcounsellors, educators, and policymakers to develop and implement effective guidance and counsellingprogrammes that better meet the needs of secondary school students.